2011
DOI: 10.1007/s00406-011-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

BDNF serum levels, but not BDNF Val66Met genotype, are correlated with personality traits in healthy subjects

Abstract: Consisting evidence in animal models has suggested that alterations in brain-derived neurotrophic factor (BDNF) brain expression and release are involved in the pathogenesis of mental illnesses, such as, mood, anxiety, and eating disorders. This hypothesis is supported by data emerging from biochemical studies on serum BDNF levels and genetic studies on the functional polymorphism Val66Met in the BDNF gene in patients and control subjects. Anxiety-related personality traits are associated with several mental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
5
35
2
3
Order By: Relevance
“…These findings suggest that the BDNF Val66Met polymorphism does not have a direct effect on AS. This finding is in line with studies that have found no significant direct association between BDNF Val66Met polymorphism and personality traits such as neuroticism or harm avoidance and anxiety disorders or mood disorders, including OCD, panic disorder, PTSD and depression (Arias et al, 2012; Chen et al, 2013; Frustaci et al, 2008; Hong et al, 2012; Minelli et al, 2011; Surtees et al, 2007; Terracciano et al, 2010), despite some studies reporting such associations (Frustaci et al, 2008; Lang et al, 2005; Min et al, 2013; Montag et al, 2010; Sen et al, 2003; Terracciano et al, 2010). Firstly, the grouping of Met66 allele carriers (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings suggest that the BDNF Val66Met polymorphism does not have a direct effect on AS. This finding is in line with studies that have found no significant direct association between BDNF Val66Met polymorphism and personality traits such as neuroticism or harm avoidance and anxiety disorders or mood disorders, including OCD, panic disorder, PTSD and depression (Arias et al, 2012; Chen et al, 2013; Frustaci et al, 2008; Hong et al, 2012; Minelli et al, 2011; Surtees et al, 2007; Terracciano et al, 2010), despite some studies reporting such associations (Frustaci et al, 2008; Lang et al, 2005; Min et al, 2013; Montag et al, 2010; Sen et al, 2003; Terracciano et al, 2010). Firstly, the grouping of Met66 allele carriers (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with the Val66 allele, the Met66 allele is associated with a decrease in activity-dependent secretion of BDNF (Egan et al, 2003). BDNF has received attention due to its evident role in anxiety and mood disorders (Angelucci et al, 2014; Hemmings et al, 2008; Li, Chang, & Xiao, 2016; Martinowich et al, 2007; Molendijk et al, 2014; Suliman, Hemmings, & Seedat, 2013), although findings have been inconsistent across studies (Frustaci, Pozzi, Gianfagna, Manzoli, & Boccia, 2008; Hong, Liou, & Tsai, 2012; Lam, Cheng, Hong, & Tsai, 2004; Minelli et al, 2011; Notaras et al, 2015; Surtees et al, 2007; Wang et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, low serum brain-derived neurotrophic factor (BDNF) levels reliably identify V animals after the first hit 5 as reported in human. [7][8][9] This experimental protocol thus provides an ideal situation to study the mechanisms of vulnerability to depression since we have access to two populations with different allostatic loads and to a predictive biomarker at a stage when none of the animals express a depression-like phenotype (that is, after SD, but before CMS).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic association studies, however, have yielded conflicting results, as higher [7,8], lower [9] and similar [10,11] BDNF levels in Met allele carriers of the Val66Met polymorphism were shown. Inconsistencies may be explained by psychopathology, race and/or gender.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies may be explained by psychopathology, race and/or gender. First, two studies investigating the relationship between genotype and serum BDNF levels were performed in depressed subjects [9,11]; others were performed in healthy subjects [7,8,10]. Secondly, two studies were carried out in Asian populations [10,11]; others comprised Caucasians only [7,8,9].…”
Section: Introductionmentioning
confidence: 99%